Determinants of Halal Cosmetics Purchase Intention: Behavioral Economics Perspective - Qonita; Paksi, Girindra Mega (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study is motivated by the rapid growth of the halal cosmetics industry and the increasing complexity of consumer decision-making, which is not solely driven by economic factors. It aims to examine the influence of income, age, credibility cues, social proof, and halal certification salience on halal cosmetics purchase intention, with perceived risk as a mediating variable. A quantitative approach was employed using a survey of 155 female halal cosmetics users in Malang City, selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that income and age do not have a significant effect on perceived risk or purchase intention. In contrast, credibility cues, social proof, and halal certification salience significantly reduce perceived risk and enhance purchase intention. These findings highlight the critical role of trust-related factors in shaping consumer behavior and provide implications for businesses to strengthen marketing strategies based on credibility, social proof, and clear halal certification.